PLANNING OF LAKE TOBA TOURISM DESTINATIONS IN TAMBUNAN VILLAGE WITH A CONTEMPORARY ECO-TOURISM APPROACH - Mayaman Maruli H. Tambunan; Bhakti Alamsyah (INFOKUM, 2022)
For this time, Lake toba is one of many tourism development area included in the National Tourism Strategic Area which is stated in Government Regulation Number 50 of 2011 about National Tourism Development Master Plan 2020. Therefore, this research has the aim of being a tourism residential facility that meets the requirement of liveable houses and tourism. The research aims to plan and design tourism supporting residential facilities (homestay) the requirements for liveable housing, tourism standards and local wisdom in the lake toba. This activity takes place during September -December 2020. The method used is a surcey of existing conditions, and architectural planning analysis